Difference between revisions of "009B Sample Midterm 3, Problem 4"

From Math Wiki
Jump to navigation Jump to search
 
Line 1: Line 1:
<span class="exam"> The rate of reaction to a drug is given by:
+
<span class="exam"> Compute the following integrals:
  
::<math>r'(t)=2t^2e^{-t}</math>
+
<span class="exam">(a) &nbsp; <math>\int x^2\sin (x^3) ~dx</math>  
  
<span class="exam">where &nbsp;<math style="vertical-align: 0px">t</math>&nbsp; is the number of hours since the drug was administered.
+
<span class="exam">(b) &nbsp; <math>\int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2(x)\sin (x)~dx</math>
 +
<hr>
 +
[[009B Sample Midterm 3, Problem 4 Solution|'''<u>Solution</u>''']]
  
<span class="exam">Find the total reaction to the drug from &nbsp;<math style="vertical-align: -1px">t=1</math>&nbsp; to &nbsp;<math style="vertical-align: 0px">t=6.</math>
 
  
 +
[[009B Sample Midterm 3, Problem 4 Detailed Solution|'''<u>Detailed Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;
 
|-
 
|If we calculate &nbsp;<math style="vertical-align: -14px">\int_a^b r'(t)~dt,</math>&nbsp; what are we calculating?
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; We are calculating &nbsp;<math style="vertical-align: -5px">r(b)-r(a).</math>&nbsp; This is the total reaction to the 
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; drug from &nbsp;<math style="vertical-align: 0px">t=a</math>&nbsp; to &nbsp;<math style="vertical-align: 0px">t=b.</math>
 
|}
 
  
 
'''Solution:'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|To calculate the total reaction to the drug from &nbsp;<math style="vertical-align: -1px">t=1</math>&nbsp; to &nbsp;<math style="vertical-align: -4px">t=6,</math>
 
|-
 
|we need to calculate
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\int_1^6 r'(t)~dt=\int_1^6 2t^2e^{-t}~dt.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|We proceed using integration by parts.
 
|-
 
|Let &nbsp;<math style="vertical-align: 0px">u=2t^2</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^{-t}dt.</math>
 
|-
 
|Then, &nbsp;<math style="vertical-align: -1px">du=4t~dt</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">v=-e^{-t}.</math>
 
|-
 
|Then, we have
 
|-
 
|&nbsp;&nbsp; &nbsp; &nbsp; <math style="vertical-align: -14px">\int_1^62t^2e^{-t}~dt=\left. -2t^2e^{-t}\right|_1^6+\int_1^6 4te^{-t}~dt.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|Now, we need to use integration by parts again.
 
|-
 
|Let &nbsp;<math style="vertical-align: 0px">u=4t</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^{-t}dt.</math>
 
|-
 
|Then, &nbsp;<math style="vertical-align: -1px">du=4dt</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">v=-e^{-t}.</math>
 
|-
 
|Thus, we get
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int_1^62t^2e^{-t}~dt} & = & \displaystyle{\left. (-2t^2e^{-t}-4te^{-t})\right|_1^6+\int_1^6 4e^{-t}}\\
 
&&\\
 
& = & \displaystyle{\left. (-2t^2e^{-t}-4te^{-t}-4e^{-t})\right|_1^6}\\
 
&&\\
 
& = & \displaystyle{(-2(6)^2e^{-6}-4(6)e^{-6}-4e^{-6})-(-2(1)^2e^{-1}-4(1)e^{-1}-4e^{-1})} \\
 
&&\\
 
& = & \displaystyle{\frac{-100+10e^5}{e^6}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; &nbsp;&nbsp; <math>\frac{-100+10e^5}{e^6}</math>
 
|}
 
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:35, 12 November 2017

Compute the following integrals:

(a)  

(b)  


Solution


Detailed Solution


Return to Sample Exam